Tobacco Usage Pattern and Its Determinants among the Students of a Medical College in Kerala - M Madhusudan; BP Sudarshan; T V Sanjay; Arun Gopi; U Gitanjali (Medsci Publications, 2017)
Background: Tobacco consumption by medical students could have negative impact on society. The study was conducted to assess the prevalence, pattern and determinetns of tobacco use among the undergraduate medical students and also their awareness towards the harmful effects of tobacco use. Methodology: This was a cross sectional observational study conducted among the undergraduate medical students of the DM Wayanad Institute of Medical Sciences, Wayanad between March-August 2017. Sample size was 400. Data were collected using a pre designed, pre tested, self administered questionnaire. Results: 18.8% were ever users and 11.8% were current users of tobacco. Current use of tobacco was higher among males compare to female, NRI quota students compared to other quota students and those with a family history of tobacco use compared to those without and all these associations were found to be statistically significant (P<0.01 for all). Average amount spent on tobacco use was Rs. 54.02±9.88 per day. The most common reason for initiating tobacco use was peer pressure (57.4%), followed by desire to experiment (48.9%) and stress relief (34%). 27.8% had inadequate knowledge about the harmful effects of tobacco use. Conclusions: The prevalence of both ever use and current use of tobacco was lower in this study. Male sex, NRI quota of admission and presence of family history of tobacco were found to have a significant association with current use of tobacco.